Comparison of the Effects of Oxytetracycline and Penicillin-Streptomycin in the Treatment of Footrot in Sheep - Sagliyan, Aydin; Gunay, Cihan; Han, Mehmet Cengiz (Medwell Online, 2008)
The purpose of this study is to determine the effects of penicillin+streptomycin (Reptopen-S, Sanofi Dogu Ilac AS) and oxytetracycline (Primamycin/LA, Pfizer) in the treatment of footrot in sheep. Footrot is an acute or subacute necrotic infectious disease in sheep. If the treatment is delayed, it can be chronic. The first symptom of the disease is lameness. Ultimately, crevices in the interdigital skin, a bad odor and necrosis are observed. Footrot is among the most serious foot diseases, which causes economic loss in sheep and call be observed in sheep of all ages. In this study it was found that sheep fold and shelter conditions were not suitable for sheep farming and farmers did not pay enough attention to foot diseases. In the treatment of infected sheep in farms, 20 mg kg(-1) oxytetracycline or 20.000 IU kg(-1) procaine benzylpenicillin + 20 mg kg(-1) dihydrostreptomycin was used as i.m. At the end of the treatment it was found that 45% of the sheep in group A, 92.5% of the sheep in group B and 95% of the sheep in group C were treated.
Keywords: Sheep; footrot; treatment; oxytetracycline; pencillin-streptomycin